2013
DOI: 10.1103/physrevb.88.125432
|View full text |Cite
|
Sign up to set email alerts
|

Probing the generalized magicity of Ag nanoclusters constructed on Si(111) by atomic manipulation

Abstract: Using scanning tunneling microscopy supplemented with first-principles calculations, we examine all the thermally activated atomistic processes of Ag n (n = 1-26) constructed atom-by-atom on a Si(111)-(7 × 7) substrate, and we exploit such cluster dynamical information to further determine the energetic stability (or magicity) of the clusters. By generalizing the traditional concept of cluster magicity solely based on cluster association/dissociation to also include various complex collective cluster motions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Furthermore, the atomic manipulation in other operating conditions such as a single atom in an ionic crystal surface [5] is quite difficult. As a result, some novel mechanisms of atomic manipulation were proposed, such as thermally activated electron attachment [6], generalised magicity of nanoclusters [7], electronic excitation of the atom or molecule [8] and so forth. Recently, IBM Research has firstly demonstrated a reversible Bergman cyclisation by the means of atom manipulation [9], which is considered as a new height in atomic manipulation, looking forward to opening up a new field of radical chemistry for on‐surface reactions by atomic manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the atomic manipulation in other operating conditions such as a single atom in an ionic crystal surface [5] is quite difficult. As a result, some novel mechanisms of atomic manipulation were proposed, such as thermally activated electron attachment [6], generalised magicity of nanoclusters [7], electronic excitation of the atom or molecule [8] and so forth. Recently, IBM Research has firstly demonstrated a reversible Bergman cyclisation by the means of atom manipulation [9], which is considered as a new height in atomic manipulation, looking forward to opening up a new field of radical chemistry for on‐surface reactions by atomic manipulation.…”
Section: Introductionmentioning
confidence: 99%